Rancangan Sistem Internal Dan Pencatatan Akuntansi Berbasis Microsoft Access Pada Cv Multilab Batam Raya - Edi Edi; Nindiatri Anandita (ConCEPt - Conference on Community Engagement Project, 2021)
The purpose of implementing this practical work is to create a system of accounting records in the form of neatly structured financial reports to make it easier for business owners to make decisions. The method used in the implementation of this practical work is the method of interviewing, observing, and collecting documents.The implementation of this practical work presents an accounting recording system using Microsoft Office Access Software to record all financial transaction which will be in the form of reports containing profit and loss, balance reports, ledger reports, financial position reports, sales reports, purchase reports, receivables reports, debt payment reports, and inventory remaining reports.The results of this accounting recording system design will be implemented to see the extent to which the system can be used as a tool CV MULTILAB BATAM RAYA in carrying out financial records.